Get low [videorecording (DVD)] - Schneider, Aaron (Aaron E.); Duvall, Robert; Spacek, Sissy; Murray, Bill, 1950 September 21-; Black, Lucas, 1982-; McRaney, Gerald (Sony Pictures Home Entertainment, 2011)
Felix Bush, a Tennessee hermit, is either feared or hated by most of the people that live in the town. One day, he gets the idea to throw one big bash before he kicks the bucket. While he is still alive and kickin' he plans his very own rollicking funeral party.